The Role of Husbands as a Support System in the Success of Exclusive Breastfeeding at Cerenti Primary Health Center, Kuantan Singingi Regency - Luci Indra; Ahmad Hafizullah Ritonga; Ika Nur Saputri (Fakultas Kesehatan Masyarakat Institut Kesehatan Medistra Lubuk Pakam, 2026)
Optimal health is an essential foundation of human development and is strongly influenced by nutritional status. Exclusive breastfeeding during the first six months of life has been scientifically proven to reduce infant morbidity and mortality, improve nutritional status, and support cognitive development and the immune system of children. However, the coverage of exclusive breastfeeding in Indonesia remains suboptimal due to various social, cultural, economic, and structural factors. This study employed a qualitative approach with a phenomenological design to explore the experiences of mothers and husbands in practicing exclusive breastfeeding. A total of 13 informants were involved, consisting of breastfeeding mothers, husbands, and healthcare providers. Data were collected through in-depth interviews, focus group discussions (FGD), limited observation, and documentation. The findings showed that most mothers understood exclusive breastfeeding as providing only breast milk without any additional food or drink for the first six months of life. Husbands generally had a more general understanding of the concept and guidelines of exclusive breastfeeding. Mothers perceived exclusive breastfeeding as an experience that not only benefits infant health but also fosters emotional bonding, satisfaction, and pride in fulfilling their maternal role. In contrast, husbands tended to emphasize the health benefits for the infant and the economic savings for the family. Family and environmental influences also contributed to strengthening the success of exclusive breastfeeding practices. Husband support was identified as a key factor and included emotional, instrumental, informational, and appreciation-based support. Emotional support was demonstrated through empathy and encouragement, instrumental support through assistance with household tasks and infant care, informational support through efforts to seek appropriate information, and appreciation support through recognition of the mother’s efforts. All forms of support contributed to increasing mothers’ sense of security, confidence, and resilience in practicing exclusive breastfeeding. Overall, husband support plays an important role in the success of exclusive breastfeeding by strengthening mothers emotionally, practically, and socially.